Design and Development of Pet Cage Ordering System on Web Based Technology - Chia, Anael Aine; Mahdin, Hairulnizam; Mohammad Syafwan Arshad (Applied Information Technology And Computer Science, 2022)
The online web-based Pet Cage Ordering system is proposed and developed for the shop Absolutely Hamster as the system admin and the welcoming customers as the system users that sell both online and physically in Johor Bahru, Johor. A questionnaire of the Google form is filled by the shop manager shows that all the orders’ data are recorded by handwriting on the papers or notebook and kept as documentary in the files, also the ordering processed by chat via social media easier makes wrong message received, missed order, wrong manually calculation total price and wrong remark taken. This proposed project is planned to manage the online business for the shop and ease the ordering process for the customers. The main language of PHP and the Waterfall Methodology are used in the system development. All the essential points and details about the proposed system development are reviewed in this paper.